2018
DOI: 10.1111/jpc.14222
|View full text |Cite
|
Sign up to set email alerts
|

Blood transfusion for anaemia of prematurity: Current practice in Australia and New Zealand

Abstract: Aim To characterise the current transfusion practice among clinicians in Australasian neonatal units and factors that influence their decision‐making. Methods Members of the Australia and New Zealand Neonatal Network (ANZNN) and practitioners at their local institutions were invited to participate in a 15‐question web‐based survey between 1 June and 31 July 2016. The survey was designed to assess (i) haemoglobin‐based transfusion thresholds; (ii) presence of local guidelines; (iii) preference for a restrictive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
1
10
0
1
Order By: Relevance
“…Thus, younger infants on more invasive respiratory support receive RBC transfusions at a higher threshold than older infants who are almost ready for discharge (Table ). In addition, neonatologists may utilise clinical signs and symptoms of anaemia to determine whether RBC transfusion is indicated (Saito‐Benz et al , ). Pre‐term infants who demonstrate increased frequency and duration of apnoea and bradycardic episodes, increased oxygen requirements, unexpected escalation of respiratory support, poor feed tolerance and growth, pallor or reduced activity may be considered to have symptomatic anaemia in need of RBC transfusion (Keyes et al , ).…”
Section: When Do We Give Rbc Transfusions For Anaemia Of Prematurity?mentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, younger infants on more invasive respiratory support receive RBC transfusions at a higher threshold than older infants who are almost ready for discharge (Table ). In addition, neonatologists may utilise clinical signs and symptoms of anaemia to determine whether RBC transfusion is indicated (Saito‐Benz et al , ). Pre‐term infants who demonstrate increased frequency and duration of apnoea and bradycardic episodes, increased oxygen requirements, unexpected escalation of respiratory support, poor feed tolerance and growth, pallor or reduced activity may be considered to have symptomatic anaemia in need of RBC transfusion (Keyes et al , ).…”
Section: When Do We Give Rbc Transfusions For Anaemia Of Prematurity?mentioning
confidence: 99%
“…However, these symptoms are highly non‐specific and may be caused by a number of other conditions, including chronic lung disease, sepsis and other pre‐term‐associated morbidities. Although RBC transfusion to treat ‘symptomatic’ anaemia of prematurity is well intended, many neonatologists report no objective clinical improvement following transfusion (Saito‐Benz et al , ).…”
Section: When Do We Give Rbc Transfusions For Anaemia Of Prematurity?mentioning
confidence: 99%
See 1 more Smart Citation
“…It is essential that processes are in place to ensure safe and appropriate transfusion decision-making, consent, documentation and administration in this vulnerable population. However, in a recent study, Australian and New Zealand neonatal units were found to have significant variation in red cell clinical transfusion practices and local policies 9. This PBE-CPI project confirmed the varied practice and inconsistent documentation practices in the NICU.…”
Section: Discussionmentioning
confidence: 59%
“…Despite a growing body of research on RBC transfusion practices, the literature reports significant variation in practices on the following issues: choosing the optimal threshold at which to administer the RBC transfusion (restrictive vs. liberal vs. historical recommendations such as maintaining Hb above 10 g/L in unwell preterm infants); use of Hct versus Hb levels as a trigger to initiate transfusion; and incorporation of noninvasive bedside monitoring devices to aid clinical decision making.…”
mentioning
confidence: 99%